The Impact of Quality Dimensions and Some Other Critical Factors on Consumers’ Furniture Purchasing Decisions - İnce, Melike Nur; Tasdemir, Cagatay (My University, 2024)
This research examined the influence of quality dimensions and various other factors on consumer choices in the Turkish furniture market, aiming to bridge a literature gap by leveraging theoretical insights and empirical data. Utilizing a detailed survey, the study captured consumer perceptions of factors influencing furniture purchases, focusing on Garvin's eight quality dimensions: Suitability, Perceived Quality, Features, Aesthetics, Service, Durability, Reliability, and Performance. The methodology included a 19-question survey targeting Bursa's population to gather data on demographic characteristics and purchasing influences, which was analyzed via Microsoft Excel. The findings underscored the paramount importance that consumers placed on durability and performance, suggesting a pragmatic approach to furniture buying where functionality trumped aesthetics. A notable preference for sustainable and eco-friendly furniture emerged, aligning with broader environmental trends. Demographically, most respondents were young, university-educated adults, indicating a market segment with distinct tastes and preferences, particularly toward modern-style furniture. These insights advocated for furniture industry stakeholders to adopt marketing strategies emphasizing product durability, performance, and environmental friendliness, aligning with consumer expectations for quality and sustainability. This alignment could be crucial for guiding product development and design to cater to contemporary consumer needs.
Keywords: Purchasing; Furniture industry; Consumer preferences; Decisions; Quality dimensions